2021
DOI: 10.2478/orga-2021-0016
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Workload, Nepotism, Job Satisfaction, and Organizational Politics on Turnover Intention: A Conservation of Resources Perspective

Abstract: Background: Despite extensive research on employee turnover intention in the existing literature. Previous studies have paid rare attention to the role of workload (WL), nepotism (N), job satisfaction (JS), and organization politics (OP) on turnover intention, especially, mediating the effect of harassment between WL, N, JS and OP on turnover intention in the Pakistani context. This study is using Hobfoll’s conservation of resources (COR) theory. Methods: Data were collected f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 56 publications
(55 reference statements)
0
6
0
1
Order By: Relevance
“…Nurses and physicians highlighted the issue of organizational nepotism that entailed discrimination and bias based on personal acquaintances, political connections, and sometimes religion. Consistently, health professionals in Turkey (Ay & Oktay, 2020; Yavuz et al, 2020), Pakistan (Abbas et al, 2021), and Saudi Arabia (Shubayra et al, 2022) also highlighted that nepotism is common in health care settings and resulted in a negative workplace environment, lack of trust and conflicts among professionals and management, and job dissatisfaction and attrition. These findings underscore the malpractice and power abuse of administrators and managers during the pandemic as experienced by frontline nurses and physicians.…”
Section: Discussionmentioning
confidence: 99%
“…Nurses and physicians highlighted the issue of organizational nepotism that entailed discrimination and bias based on personal acquaintances, political connections, and sometimes religion. Consistently, health professionals in Turkey (Ay & Oktay, 2020; Yavuz et al, 2020), Pakistan (Abbas et al, 2021), and Saudi Arabia (Shubayra et al, 2022) also highlighted that nepotism is common in health care settings and resulted in a negative workplace environment, lack of trust and conflicts among professionals and management, and job dissatisfaction and attrition. These findings underscore the malpractice and power abuse of administrators and managers during the pandemic as experienced by frontline nurses and physicians.…”
Section: Discussionmentioning
confidence: 99%
“…The second stream of research focuses on the relationship between nepotism and employees’ attitudes and behaviors. Research has found that nepotism is related to higher employee job dissatisfaction (Abbas et al. , 2021; Arasli et al.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although previous research has examined the relationship between job satisfaction and nepotism (e.g. Abbas et al. , 2021; Daskin et al.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Hasil uji asumsi klasik 1. Penelitian ini memiliki hasil bahwa variabel kepuasan kerja memiliki pengaruh terhadap turnover intention (10) . Sehingga apabila kepuasan kerja meningkat satu satuan maka turnover intention akan menurun sebesar satu satuan.…”
Section: Hasil Dan Pembahasanunclassified